A fast forward error correction allocation algorithm for unequal error protection of video transmission over wireless channels - Chang, Yoong; Lee, Sze; Komyia, Ryoichi (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
A new fast forward error correction (FEC) allocation algorithm for unequal error protection (UEP) of video transmission over wireless channels is proposed in this paper. First, an UEP scheme, which takes into consideration the non-uniformly distributed importance of frames in a group of pictures (GOP) and macroblocks in a video frame, is proposed. An enhanced video error propagation model, namely expected number of macroblocks error propagation (ENMEP) is also proposed in this paper to measure the amount of error propagation caused by transmission errors. Finally, by making use of our proposed ENMEP error propagation model, a fast FEC allocation algorithm for our proposed UEP scheme is also proposed. Simulation results demonstrate that our scheme outperforms the previous UEP scheme and the classical equal error protection (EEP) scheme.